Case report: Immunotherapy guided by molecular profiling of tumors: illustrative cases and literature review - Ozdogan, Mustafa; Papadopoulou, Eirini; Metaxa-Mariatou, Vasiliki; Kapetsis, George; Meintani, Angeliki; Florou-Chatzigiannidou, Chrysiida; Yildiz, Akin; Cakir, Muharrem Okan; Kirca, Onder; Nasioulas, George (Frontiers in Medicine, 2024)
Predictive biomarkers are necessary for the identification of immunotherapy-responsive patients. Tumor Mutation Burden (TMB), as determined by Next Generation Sequencing (NGS), and PD-L1 expression, as evaluated by Immunohistochemistry, are the biomarkers most frequently employed in clinical practice. In addition, Microsatellite Instability (MSI) was the first biomarker to demonstrate immunotherapy efficacy irrespective of tumor type and possesses a high predictive value. However, its limited prevalence across most tumor types limits its therapeutic potential. Two cancer patients with positive TMB and PD-L1 expression are described in this report. The molecular profile of the tumor indicated that the first case was responsive to ICI, while the second case was resistant.Combined with immunotherapy predictive biomarkers such as PD-L1 expression and TMB, these examples demonstrate that tumor molecular analysis can enhance the prediction of ICI response for specific patients. This methodology enables an individualized and improved approach to the treatment and management of the disease.